Typology and structural characteristics of the woody population of oasian basins in south-eastern Niger - Soumana, Douma; Illiassou, Salamatou Abdourahamane; Mamoudou, Boubacar Moussa; Gazali, Daouda; Tidjani, Adamou Didier; Mahamane, Ali (International Journal of Environment, Agriculture and Biotechnology, 2021)
The present study aims to characterize the typology of woody stands in oasis basins in the Gouré department: the case of Balla, Kilakina and Tchago. In these oasian basins, 75 survey plots of 50x50m² were carried out in order to collect informations about le floral of the area and its dendrometric characteristics. The woody stand of the basins contains a total of 26 woody species divided into 23 genera and 16 different families. The most represented families are: Mimosaceae (7 species or 26%), Arecaceae (2 species or 7.79%), Asclepiadaceae (2 species or 7.79%), Anacardiaceae (2 species or 7.79%) and Myrtaceae (2 species or 7.79%).The characterization of the woody stand of the oasis basins of Gouré according to the importance value index showed that Hyphaene thebaica (L.) Mart has the highest contribution (852.7 points), and Adansonia digitata L., the least (59.28 points). Three plant groups were identified based on the ascending hierarchical classification from 15% similarity and the dendrometric structure of each group was established. The later defined a positive asymmetric distribution characterizing the dominance of young individuals. Based on the above results, the diversity of the oasian basins is high. Nevertheless, this biodiversity is exposed to severe climatic conditions and anthropogenic pressure, which makes its vulnerability. In this circumstance, our study remains as a tool for better management and exploitation of this woody stand.